Reliability estimation of universal stand for tests of hydraulic units - Андренко, Павло Миколайович; Клітной, Володимир Вікторович; Погорєлов, Денис Сергійович (Technology audit and production reserves, 2016)
The object of research is universal energy-efficient stand for tests of hydraulic units of different types, distinguishing feature of it is the use of an adjustable axial piston pump and piston hydro-pneumatic accumulator. Determination of reliability of such stand on the stage of its design will allow a reasonable choice to hold hydraulic equipment and units for its implementation. During the research it was built its block diagram. Using the method of block diagrams, an analytical dependence for calculating the probability of failure-free operation of the stand was obtained. Probability and the average time of failure-free operation for different values of the failure rate were established. An accuracy of the calculations was estimated. It was shown that the proposed universal stand for tests of hydraulic units is the system with a high level of reliability.